Pengembangan Bahan Ajar Tema Permainan Tradisional Berbasis Kearifan Lokal Tana Luwu di Sekolah Dasar - Sahdania; Nurdjan, Sukirman; Hisbullah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study focuses on the development of teaching materials for traditional games based on the local wisdom of Tana Luwu. The aim is to analyze needs, develop, validate, and evaluate the practicality of the developed teaching materials. The research adopts a Research and Development (R&D) approach with the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation, albeit only reaching the implementation stage (trial). Research instruments involve teacher interviews and student questionnaires. The produced teaching materials are validated by three validators (design, content, language). Data analysis incorporates both qualitative and quantitative methods. The needs analysis indicates that students at SDN 92 Karetan require teaching materials for local traditional games. The teaching materials are in print form and are validated by experts with an average percentage of 90.21%. The practicality questionnaire for students reveals a practicality level of 90.22%, categorized as highly practical. In conclusion, after undergoing the development stages, these teaching materials are deemed suitable for enhancing students' understanding in the school learning process.